사지마비를 주소로 하는 길랑바레 증후군 환자에 대한 증례보고 1례 - 허기윤; 이찬; 조임학; 강희경; 김민화; 김소연; 박성하; 윤영주; 이인; 최준용; 한창우; 홍진우; et al. (대한한방내과학회지, 2021)
Purpose: The aim of this study was to report the improvement of Guillain-Barre syndrome after long-term combination treatment with Korean medicine. Methods: A patient was diagnosed with Guillain-Barre syndrome and treated with herbal medicine, acupuncture, pharmacopuncture, moxibustion, and exercise, including quadruped walking after three hospital admissions. To evaluate muscle strength and weakness, we measured manual muscle function, gait pattern, and the speed of quadruped walking. Results: The patient's muscle weakness in the extremities and gait stance were improved. The speed of quadruped walking was increased. Conclusion: We consider that combined treatment with Korean medicine might be effective for the muscle weakness of Guillain-Barre syndrome with a poor prognostic factor. To verify the effectiveness of this treatment, further research is needed.